Differences in Self-Esteem among the Eighth Grade Students of Different Genders and Their Impact toward Students’ Speaking Skills (A Case Study at SMPN 19 Palembang) - Dhia Fitriah; Rusman Roni (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: The objectives of the study were to find out if (1) there was any significant difference in self-esteem among the students of different genders, (2) there was any significant difference in speaking skills among the students of different genders, (3) there was any significant influence of self-esteem toward students’ speaking skills, (4) how much the contribution of self- esteem toward the students’ speaking. The study was conducted at SMPN 19 Palembang. The population and sample of the study was the eighth-grade students academic year 2019/2020. The data were collected by using questionnaire and speaking test which would be analyzed by applying the correlational and regression analyses using SPSS version 26.0. It was found out that there was no significant difference in self-esteem among the students of different genders where t-obtained (1.492) lower than the value of t-table (2.021) with df= 40. However, there was significant difference in speaking skills among the students of different genders where the value of t-obtained (4.052) higher than the value of t-table (2.021). It was also found that there was significant correlation between self-esteem and speaking skill. The Correlation Coefficient was0.341 at (p) 0.031. Additionally, further analysis using the linear regression analysis revealedthat self-esteem contributed 11.6% to speaking skills. Keywords: correlation, self-esteem, gender, speaking skills Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui apakah (1) terdapat perbedaan yang signifikan antara harga diri siswa dengan gender yang berbeda, (2) terdapat perbedaan yang signifikan dalam keterampilan berbicara di antara siswa dengan gender yang berbeda, (3) terdapat pengaruh yang signifikan pada harga diri terhadap keterampilan berbicara siswa, (4) seberapa besar kontribusi harga diri siswa terhadap keterampilan berbicara siswa. Penelitian dilakukan di SMPN 19 Palembang. Populasi dan sampel penelitian adalah siswa kelas delapan tahun ajaran 2019/2020. Pengumpulan data dilakukan dengan menggunakan angket dan tes berbicara yang kemudian dianalisis dengan menerapkan analisis korelasional dan regresi menggunakan SPSS versi 26.0. Ditemukan bahwa tidak ada perbedaan yang signifikan pada harga diri dengan nilai t diperoleh (1.492) lebih rendah dari nilai t-tabel (2.021) dengan df = 40. Namun terdapat perbedaan yang signifikan keterampilan berbicara pada siswa dengan gender yang berbeda, dimana nilai t yang diperoleh (4.052), lebih tinggi dari nilai t-tabel (2.021). Ditemukan juga bahwa terdapat hubungan yang signifikan antara harga diri dan keterampilan berbicara. Koefisien korelasi yang ditemukan adalah 0.341 pada (p) 0.031. Selain itu, analisis lebih lanjut menggunakan analisis regresi linier mengungkapkan bahwa kepercayaan diri berkontribusi 11,6% terhadap keterampilan berbicara. Kata-kata kunci: korelasi, harga diri, gender, keterampilan berbicara